Faktor yang Berhubungan dengan Perawatan Payudara pada Ibu Nifas - Pratiwi Nasution (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Breast care is an action to care for the breasts especially during the postpartum period (breastfeeding period) to facilitate the release of breast milk. Based on the results of a preliminary survey, there are still many postpartum mothers who do not understand about breast care. The purpose of this study was to determine the factors related to breast care in postpartum mothers. The design used in this study was a descriptive analytical survey with a cross-sectional approach. The population in this study as the subject of the case was all postpartum mothers as many as 30 respondents with a population sampling technique. Data analysis used univariate and bivariate analysis with the Chi Square test. The results of the study showed that there was a relationship between age and breast care obtained p-value: 0.015, there was a relationship between attitude and breast care with p-value: 0.016 and there was a relationship between husband's support and breast care with p-value: 0.007. It is hoped that the results of this study can be used as input and useful information regarding breast care.